Developing a visual novel for public sector accounting course at UiTM Kedah: A brief note / Intan Marzita Saidon, Saluana Che Salleh and Nadzri Ab Ghani - Saidon, Intan Marzita; Che Salleh, Saluana; Ab Ghani, Nadzri (Universiti Teknologi MARA, Kedah, 2019)
This paper describes the development process of a visual novel as a teaching aid for the Public Sector Accounting course at UiTM Kedah. A visual novel is an interactive game genre, which originated in Japan. Application of a visual novel as a teaching aid could be considered as an innovative way of teaching a "dry" subject like public sector accounting. Three stages involved in the development process of the visual novel. The first two stages were concerned with the physical development of the visual novel. Using conveniently selected respondents, an assessment regarding the usage of the visual novel as a teaching aid was carried out in the third stage. Findings indicated that a visual novel has great potential in enhancing students' understanding and sustained their engagement in learning the Public Sector Accounting course.